Psychosocial concerns reported by Syrian refugees living in Jordan: Systematic review of unpublished needs assessments - Wells, Ruth; Steel, Zachary; Abo-Hilal, Mohammad; Hassan, Abdul Halim; Lawsin, Catalina (British journal of psychiatry, 2016)
Humanitarian organisations supporting Syrian refugees in Jordan have conducted needs assessments to direct resources appropriately. To present a model of psychosocial concerns reported by Syrian refugees and a peer review of research practices. Academic and grey literature databases, the United Nations Syria Regional Response website, key humanitarian organisation websites and Google were searched for needs assessments with Syrian refugees in Jordan between February 2011 and June 2015. Information directly reporting the views of Syrian refugees regarding psychosocial needs was extracted and a qualitative synthesis was conducted. Respondents reported that psychological distress was exacerbated by both environmental (financial, housing, employment) and psychosocial outcomes (loss of role and social support, inactivity), which are themselves stressors. Need for improvement in research methodology, participatory engagement and ethical reporting was evident. Participatory engagement strategies might help to address identified psychosocial outcomes. More rigorous qualitative methods are required to ensure accuracy of findings.